PERAN JAPAN INTERNATIONAL COOPERATION AGENCY (JICA) DALAM PELAKSANAAN PROYEK CAPACITY BUILDING FOR RESTORATION OF ECOSYSTEM IN CONSERVATION AREA (RECA) DI TAMAN NASIONAL BROMO TENGGER SEMERU JAWA TIMUR - Jivandra Vega; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
JICA is a Japanese foreign cooperation agency to assist developing countries , by distributing grant assistance, technical cooperation, and loans. Indonesia is one of the countries that has collaborated with JICA through the RECA project, which is a capacity building project for ecosystem restoration in conservation areas and to strengthen the capacity of stakeholders to restore damaged ecosystems in Bromo Tengger Semeru National Park. This study aims to describe the role of the Japan International Cooperation Agency (JICA) in the implementation of the Capacity Building for Restoration of Ecosystem In Conservation Area Project (RECA) in Bromo Tengger Semeru National Park, East Java . Type the research used by the author is descriptive-analytic, namely research that uses a pattern of depicting empirical facts accompanied by arguments relevant to qualitative research methods. Data collection techniques are carried out through literature studies, documents and interviews. The perspective that the authors use is the fluralism perspective with the level of group analysis and the use of international organization theory.This research shows that JICA is making various efforts to overcome environmental damage in Bromo Tengger Semeru National Park through the RECA project and JICA as an international organization plays an active role as a motivator through training activities for local communities on making bricks from sedimentation mud and controlling forest fires, as communicators with ecosystem restoration seminars in conservation areas and as an intermediary through the prevention of salvinia molesta in Ranu Pani Lake, construction of sedimentation dams and planting of plant seeds in conservation areas. Keywords: The Role, JICA, RECA